The Global Redox Responding RegB/RegA Signal Transduction System Regulates the Genes Involved in Ferrous Iron and Inorganic Sulfur Compound Oxidation of the Acidophilic Acidithiobacillus ferrooxidans - Moinier, Danielle; Byrne, Deborah; Amouric, Agnès; Bonnefoy, Violaine (Frontiers in Microbiology, 2017)
The chemical attack of ore by ferric iron and/or sulfuric acid releases valuable metals. The products of these reactions are recycled by iron and sulfur oxidizing microorganisms. These acidophilic chemolithotrophic prokaryotes, among which Acidithiobacillus ferrooxidans, grow at the expense of the energy released from the oxidation of ferrous iron and/or inorganic sulfur compounds. In At. ferrooxidans, it has been shown that the expression of the genes encoding the proteins involved in these respiratory pathways is dependent on the electron donor and that the genes involved in iron oxidation are expressed before those responsible for inorganic sulfur compound oxidation when both iron and sulfur are present. Since the redox potential increases during iron oxidation but remains stable during sulfur oxidation, we have put forward the hypothesis that the global redox responding two components system RegB/RegA is involved in this regulation. To understand the mechanism of this system and its role in the regulation of the aerobic respiratory pathways in At. ferrooxidans, the binding of different forms of RegA (DNA binding domain, wild-type, unphosphorylated and phosphorylated-like forms of RegA) on the regulatory region of different genes/operons involved in ferrous iron and inorganic sulfur compound oxidation has been analyzed. We have shown that the four RegA forms are able to bind specifically the upstream region of these genes. Interestingly, the phosphorylation of RegA did not change its affinity for its cognate DNA. The transcriptional start site of these genes/operons has been determined. In most cases, the RegA binding site(s) was (were) located upstream from the -35 (or -24) box suggesting that RegA does not interfere with the RNA polymerase binding. Based on the results presented in this report, the role of the RegB/RegA system in the regulation of the ferrous iron and inorganic sulfur compound oxidation pathways in At. ferrooxidans is discussed.